McDonaldization without a McDonald's: globalization and food culture as social determinants of health in urban Bangladesh - Zaman, Shahaduz; Selim, Nasima; Joarder, Taufique (© Association for the Study of Food and Society 2013, 2016)
This article was published in Food, Culture and Society [© Association for the Study of Food and Society 2013] and the definite version is available at: http://www.tandfonline.com/doi/abs/10.2752/175174413X13758634982010